10 kHz repetition rate picosecond green laser for high-accuracy satellite ranging - Fan, Zhongwei; Liu, Xiaopeng; Zhang, Zhongping; Meng, Wendong; Long, Mingliang; Bai, Zhenao (Frontiers in Physics, 2023)
Picosecond pulse laser is the main light source for satellite laser ranging. In this paper, a 10 kHz repetition rate picosecond green laser with an average output power of 5.3 W is demonstrated. The laser generates a pulse width of 18.6 ps at a center wavelength of 532.2 nm with a spectral width of 0.066 nm. The beam quality is well preserved with M2 of 1.1 with the beam divergence measured to be 0.62 mrad and pointing stability of 7 μrad over 30 minutes of operation. The laser system was then applied to measure the BeiDou satellite (Compass-I3) and generated a single range accuracy of 3.2 mm, which is the highest reported range accuracy for synchronous orbit satellite laser ranging.